Research on Fracture Toughness of C120 Ultra-High-Performance Concrete in Kingkey Financial Center Project - Hao-Wen Ye; Nai-Qian Feng; Zhi-Wei Ran; Li-Xun Lin; Yan Ling-Hu; Shi-Kun Qi; Yi Dong (Advances in Materials Science and Engineering)
By adding polypropylene fiber, fracture toughness of C120 ultra-high-performance concrete in Kingkey Financial Center project has been enhanced. The tests conducted by the Building Material Lab of the Civil and Water Conservancy Institute of Tsinghua University provided satisfactory results of mechanical property and fracture toughness of C120 ultra-high-performance concrete.